Studies in law, politics, and society. Vol. 76 - Sarat, Austin (Studies in law, politics, and society ;, 2018)
Studies in Law, Politics, and Society provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. In this latest edition of this highly successful research series, chapters examine a diverse range of legal issues and their impact on and intersections with society. This volume features a special section with papers dedicated to law and disability. The chapters examine issues of HIV, obesity, disability rights, assisted suicide and prenatal testing. Other papers included in this important volume address the right to education for migrant children in the United States and the rights to citizenship of British children. This volume brings together leading scholars and will be vital reading for all those researching in this subject area.